The moderating influence of organisational capacity on the association between corporate governance and corporate performance - Mustapa, Ifa Rizad; Mohd Ghazali, Nazli Anum; Mohamad, Muslim Har Sani (Elsevier, 2014)
The current research examines the moderating effect of organizational capacity on the association between corporate governance and corporate performance. This research employs questionnaire survey in obtaining the data and contributes to the methodology by demonstrating the interaction terms in assessing the effect of moderators on corporate performance. Practical implication from this research is that a company needs to have adequate infrastructure and utilize it appropriately because its interaction with corporate governance is proven to have an influence on corporate performance. Findings of this research recognize that infrastructure emerges as an important element to the research of corporate governance.